2022
DOI: 10.3390/biology11111545
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining of Recombinant Camel Chymosin and Testing Its Milk-Clotting Activity on Cow’s, Goat’s, Ewes’, Camel’s and Mare’s Milk

Abstract: In the cheese-making industry, commonly chymosin is used as the main milk-clotting enzyme. Bactrian camel (Camelus bactrianus) chymosin (BacChym) has a milk-clotting activity higher than that of calf chymosin for cow’s, goat’s, ewes’, mare’s and camel’s milk. A procedure for obtaining milk-clotting reagent based on recombinant camel chymosin is proposed here. Submerged fermentation by a recombinant yeast (Pichia pastoris GS115/pGAPZαA/ProchymCB) was implemented in a 50 L bioreactor, and the recombinant camel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…The protein structure and enzyme activity are impacted by N-glycosylation. N-glycosylation of proteins produced in P. pastoris is noted, and this is followed by an increase in molecular weight [ 27 , 52 ]. In the present work, the effect of N-glycosylation on the α-amylase activity and thermal stability of α-amylase from B. licheniformis was determined, and the half-life at 80 °C is twofold shorter for glycosylated enzyme than for non-glycosylated analog.…”
Section: Discussionmentioning
confidence: 99%
“…The protein structure and enzyme activity are impacted by N-glycosylation. N-glycosylation of proteins produced in P. pastoris is noted, and this is followed by an increase in molecular weight [ 27 , 52 ]. In the present work, the effect of N-glycosylation on the α-amylase activity and thermal stability of α-amylase from B. licheniformis was determined, and the half-life at 80 °C is twofold shorter for glycosylated enzyme than for non-glycosylated analog.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant technology has been used by researchers to engineer novel chymosin enzymes with tailored properties for specific applications ( Akishev et al, 2022 , Vallejo et al, 2012 , Wei et al, 2016 ). Notably, Vallejo et al demonstrated that recombinant goat chymosin displayed superior catalytic efficiency compared to buffalo, bovine, or camel versions ( Vallejo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…From 2001 to the present, the following rChns have been obtained and characterized: sheep (Ovis aries) [13], goat (Capra hircus) [14][15][16], buffalo (Bubalus arnee bubalis) [17,18], yak (Bos grunniens) [19,20], alpaca (Vicugna pacos) [21], Altai maral (Cervus elaphus sibiricus) [22][23][24][25], rabbit (Oryctolagus cuniculus) [26], white whale (Delphinapterus leucas) [27], two-humped camel (Camelus bactrianus) [28,29], and tupaya (Tupaia belangeri chinensis) [30].…”
Section: Introductionmentioning
confidence: 99%